Konsep Nasionalisme Perspektif Syaikh Abdul Latief Syakur - Wahidi, Ridhoul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
In the state of nationalism is the spirit for every citizen. The attitudes of loving the motherland, defending the country and unity are inseparable in order to strengthen the resilience of the nation. Shaykh Abdul Latief Syakur as a local figure who lived during the colonial era, wanted to free the influence of community submission to the invaders through his interpretive work, namely Tafsīr Yā Ayyuha Al-Lażīna Āmanū. This study uses a textual and contextual approach. The nationalism spirits that emerged from this study were first the values of the struggle and progress of the nation and homeland, secondly, the principle of national defense, thirdly promoting the values of unity, and fourthly the ethical values. These four spirits are still very relevant today amid the waning efforts of the struggle and progress of the nation and the motherland, the principles of the defense of the State, the values of unity, and ethical principles in social life. The substantive values of Shaykh Abdul Latief Syakur's nationalism in his interpretation are the distinguishing values of his era's paza which can be applied to the present context